KEBIASAAN MAKANAN IKAN BUNTAL PISANG (Tetraodon lunaris) DI PERAIRAN MAYANGAN, JAWA BARAT [Study on Food Habit of Blowfish, Tetraodon lunaris in Mayangan Waters, West Java] - Tri Wahyuni; Sulistiono Sulistiono; Ridwan Affandi (Jurnal Iktiologi Indonesia, 2004)
The study was conducted to obtained food habits of blowfish, comprises relative consumption food and composition of food. Fish sample taken by dogol net with mesh size 1; 1.5 and 2.5 inchi. The collected fish was 253 males and 317 females. Fish sample taken once in month using net with mesh size 1; 1.5 and 2.5 inch. Food analysis determined by using Index Stomach Content (ISC) and Index of Preponderance. Food composition comprises fish, shells, gastropods, shrimp, crabs, squids, serasah and unintified.